Carboxyl terminal domain basic amino acids of mycobacterial topoisomerase I bind DNA to promote strand passage - Ahmed, Wareed (Oxford University Press, 2013)
Bacterial DNA topoisomerase I (topoI) carries out relaxation of negatively supercoiled DNA through a series of orchestrated steps, DNA binding, cleavage, strand passage and religation. The N-terminal domain (NTD) of the type IA topoisomerases harbor DNA cleavage and religation activities, but the carboxyl terminal domain (CTD) is highly diverse. Most of these enzymes contain a varied number of Zn(2+) finger motifs in the CTD. The Zn(2+) finger motifs were found to be essential in Escherichia coli topoI but dispensable in the Thermotoga maritima enzyme. Although, the CTD of mycobacterial topoI lacks Zn(2+) fingers, it is indispensable for the DNA relaxation activity of the enzyme. The divergent CTD harbors three stretches of basic amino acids needed for the strand passage step of the reaction as demonstrated by a new assay. We also show that the basic amino acids constitute an independent DNA-binding site apart from the NTD and assist the simultaneous binding of two molecules of DNA to the enzyme, as required during the catalytic step. Although the NTD binds to DNA in a site-specific fashion to carry out DNA cleavage and religation, the basic residues in CTD bind to non-scissile DNA in a sequence-independent manner to promote the crucial strand passage step during DNA relaxation. The loss of Zn(2+) fingers from the mycobacterial topoI could be associated with Zn(2+) export and homeostasis.